2004
DOI: 10.1111/j.1365-2966.2004.07860.x
|View full text |Cite
|
Sign up to set email alerts
|

AnXMM-Newtonobservation of the massive, relaxed galaxy cluster ClJ1226.9+3332 atz= 0.89

Abstract: A detailed X‐ray analysis of an XMM–Newton observation of the high‐redshift (z= 0.89) galaxy cluster ClJ1226.9+3332 is presented. After careful consideration of background subtraction issues, the X‐ray temperature is found to be 11.5+1.1−0.9 keV, the highest X‐ray temperature of any cluster at z > 0.6. The temperature is consistent with the observed velocity dispersion. In contrast to MS 1054−0321, the only other very hot cluster currently known at z > 0.8, ClJ1226.9+3332, features a relaxed X‐ray morphology, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
65
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 41 publications
12
65
0
Order By: Relevance
“…We find L X (r < 1:43 Mpc) ¼ 4:57 AE 0:11 ergs s À1 and L X (r < 1) ¼ 5:12 AE 0:12 ergs s À1 , including uncertainties on the temperature and metal abundance in those on the luminosity. These luminosities are consistent with those found by Maughan et al (2006b) based on a shorter XMMNewton observation of Cl J1226.9+3332.…”
Section: The Global Properties Of CL J12269+3332 and The Scaling Relsupporting
confidence: 81%
See 2 more Smart Citations
“…We find L X (r < 1:43 Mpc) ¼ 4:57 AE 0:11 ergs s À1 and L X (r < 1) ¼ 5:12 AE 0:12 ergs s À1 , including uncertainties on the temperature and metal abundance in those on the luminosity. These luminosities are consistent with those found by Maughan et al (2006b) based on a shorter XMMNewton observation of Cl J1226.9+3332.…”
Section: The Global Properties Of CL J12269+3332 and The Scaling Relsupporting
confidence: 81%
“…Cl J1226.9+3332 was detected in the Wide Angle ROSAT Pointed Survey (WARPS; Scharf et al 1997;Ebeling et al 2001), and an analysis of a 15 ks AO1 XMMNewton observation confirmed its temperature at 11:5 keV with a bolometric luminosity of 5 ; 10 45 ergs s À1 and a relaxed morphology ( Maughan et al 2004a). An early, short Chandra observation of Cl J1226.9+3332 was presented by Cagnoni et al (2001), who also pointed out that the VLA 3 FIRST catalog shows a faint pointlike radio source at the cluster center, consistent with a lowluminosity radio-loud active galactic nucleus (AGN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are suitable laboratories in which to study galaxy populations, providing clues to better understand the effects of the local environment on galaxy properties and galaxy evolution. Cluster X-ray luminosity and temperature indicate the existence of massive systems (M > 10 14 M ) already when the universe was half its present age (Jeltema et al 2001;Maughan et al 2003Maughan et al , 2004Rosati et al 2004;Mullis et al 2005). While some of these clusters have a relaxed X-ray morphology by z $ 0:8 (Maughan et al 2004), others show clear signatures of being still in a formation stage, as indicated by their filamentary morphology and the presence of substructure (Gioia et al 1999(Gioia et al , 2004Demarco et al 2005;Girardi et al 2005;Tanaka et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray selected samples at z ≥ 1 probe the most massive and dynamically relaxed systems (e.g., Maughan et al 2004;Stanford et al 2006;Bremer et al 2006;Lidman et al 2008). Large-area multicolour surveys, such as the red-sequence survey (e.g.…”
Section: Introductionmentioning
confidence: 99%